Ability of Dwarf Elephant Grass (Pennisetum purpureum Cv. Mott) and Gliricidia sepium to Capture Ammonia (NH3) Around Chicken Cages: An in vitro Evaluation - Akmal,; Jamarun, Novirman; Zain, Mardiati (Pakistan Journal of Nutrition, 2018)
Background and Objective: Manure accumulation in open areas for long periods of time promotes the synthesis of ammonia (NH3) by microbes and its emission to the atmosphere. Forage plants are used as ammonia trapsin poultry farms. This study aims to evaluate the potential of planting dwarf elephant grass and Gliricidia sepium around poultry farms to trap ammonia. Methodology: This study used a complete randomized design with a 2×3 factorial pattern with 6 replications as follows: Factor A: Two species (Dwarf elephant grass and Gliricidia sepium) and Factor B: The distance of the cages from the laying hen (1.5, 3 and 100 m). The parameters measured were the dry matter forage yield, plant height, protein content, ammonia concentration and in vitro dry matter digestibility. Results: The dry matter production of dwarf elephant grass was higher than that of Gliricidia sepium (0.5 vs 0.24 kg pot–1), but for the other parameters, such as the plant height, protein content and dry matter digestibility, the values for Gliricidia sepium were higher than those for dwarf elephant grass. Regarding the plant’s distance from the cage, a distance of 1.5 m yielded the highest levels of dry matter, forage yield, plant height, protein content and in vitro dry matter digestibility. The ammonia concentration at the cage of the laying hen was 7.7 ppm and at a distance of 3 m was 0.88 ppm. Conclusion: Gliricidia sepium was effective at absorbing air borne NH3. Plants 1.5 m from the laying hen cage showed the best results.